Vaginal progesterone in women with twin gestations complicated by short cervix: a retrospective cohort study. (27th November 2014) - Brubaker, SG; Pessel, C; Zork, N; Gyamfi‐Bannerman, C; Ananth, CV
Abstract : Objective: To determine whether the use of vaginal progesterone in twin gestations with a cervical length (CL) of ≤2.5 cm is associated with a reduced risk of preterm delivery. Design: Retrospective cohort study. Setting: Tertiary‐care medical centre in New York City. Population: Women with twin gestations undergoing sonographic cervical length screening. Methods: Women with twin gestations with a CL of ≤2.5 cm between 16 and 32 weeks of gestation, and who delivered at our centre between 2010 and 2013, were included. We evaluated the impact of vaginal progesterone on the risk of preterm delivery using a Cox proportional hazard model, adjusted for potential confounding factors. We then performed a propensity score analysis using inverse probability of treatment weights to account for treatment selection bias and confounding. Main outcome measure: Delivery prior to 35 weeks of gestation. Results: Of the 167 twin pregnancies analysed, 61 (35.7%) were treated with vaginal progesterone. The hazard ratio (HR) of delivery prior to 35 weeks of gestation in the vaginal progesterone group, compared with the no vaginal progesterone group, was 1.8 (95% confidence interval, 95% CI 1.5–3.1) in the unadjusted analysis, 1.4 (95% CI 0.7–3.2) following multivariable adjustment for confounding factors, and 1.5 (95% CI 1.1–2.3) using propensity score methods. Conclusion: Women with more risk factors for preterm delivery were more likely to be treated with vaginal progesterone. After statistically correcting for this with propensity score methods, we found that vaginal progesterone therapy in twin pregnancies with a CL ≤2.5 cm was associated with an increased risk of preterm delivery.